Zirconium retention for minimizing environmental risk: Role of counterion and clay mineral. (March 2021) - Montes, L.; Pavón, E.; Cota, A.; Alba, Maria D.
Abstract: Zr(IV) together with U(IV) are the major components of high-level radionuclide waste (HLRW) and spent nuclear fuel (SNF) from nuclear power plants. Thus, their retention in the waste disposal is of great importance for the environmental risk control. Here, the influence of clay minerals on the retention of Zr(IV), as component of the nuclear waste and as chemical analogues of U(IV), has been evaluated. Three clay minerals, two bentonites and one saponite, were hydrothermally treated with three zirconium salts. A structural study at long-range order by X-ray diffraction and short-range order by NMR was performed to evaluate the generation of new zirconium phases and degradation of the clay minerals. Three immobilization mechanisms were observed: i) cation exchange of ZrO 2+ or Zr 4+ by clay minerals, ii) the precipitation/crystallization of ZrO2, and, iii) the chemical interaction of zirconium with the clay minerals, with the formation of zirconium silicates. Graphical abstract: Image 1 Highlights: Influence of clay on Zr(IV) retention, a U(IV) chemical analogue, has been evaluated. Hydrothermal treatment not only caused the cation exchange of ZrO 2+ or Zr 4+ by clay. Main retention mechanisms were precipitation and chemical reaction.